Prevalence and factors related to anaemia in children aged 6–59 months attending a quaternary health facility in Maputo, Mozambique - Maulide Cane, Réka (2023)
Funding Information: R.M.C., L.V. and I.C. were supported by Fundação para a Ciência e a Tecnologia for funds to GHTM-UID/04413/2020. R.M.C was supported by Fundação para a Ciência e a Tecnologia for funds for her Doctoral Program (UI/BD/151065/2021). The views expressed in this paper are from the own authors and not the official position of the institutions or funder. We thank Paulino da Costa, Faizana Amad, Eugenia Macassa, Nocita da Natividade Macuacua, Amélia Guambe, Rosita Agostinho Baloi Cossa, Vasco Muchanga, Lidia Maungue, Henrique Afonso Mondlane, Silvia Panunzi and Luzia Gonçalves. We also thank the staff of the Pediatrics Department of Maputo Central Hospital. This work is dedicated to Tamim Merzouki (deceased). Publisher Copyright: © 2023 The Author(s). Published by Informa UK Limited, trading as Taylor & Francis Group.